Cytotoxic diterpenoids from the roots of Euphorbia stracheyi. (April 2020) - Ye, Ye; Liu, Guang-Hui; Dawa, Drolma; Ding, Li-Sheng; Cao, Zhi-Xing; Zhou, Yan
Graphical abstract: Highlights: Three new diterpenes were isolated from Euphorbia stracheyi . Compound 11 was an ingenane-type diterpenoid with a deca-2'' E, 4'' E, 6'' E -trien-1-one moiety. Compounds 11 and 13 exhibited significant cytotoxic activity against MV4-11 with IC50 values of 5.92 and 3.48 μ M. Abstract: Three new diterpenoids, euphstrachenols A–C (1, 2, and 11 ), together with nineteen known analogues were isolated from the roots of Euphorbia stracheyi . Compounds 1 and 2 were lathyrane-type diterpenoids with a decadienoyl acidic moiety. Compound 11 was an ingenane-type diterpenoid with a deca-2′′ E, 4′′ E, 6′′ E -trien-1-one moiety. Their structures were elucidated by comprehensive spectroscopic analyses. All the isolated compounds were evaluated in vitro for their cytotoxic activity against four human cancer cell lines and a murine cell line, and compounds 1, 2, 4, 5, 7, 9, and 11 –14 exhibited moderate cytotoxicity against MV4-11 cell line with IC50 values from 3.48 to 30.02 μ M.